Seasonal nitrogen uptake and regeneration in the western coastal Arctic. (8th May 2017) - Baer, Steven E.; Sipler, Rachel E.; Roberts, Quinn N.; Yager, Patricia L.; Frischer, Marc E.; Bronk, Deborah A.
Abstract: Here, we present the first study to investigate the seasonal importance of amino acid‐nitrogen (N) to Arctic near shore microbial communities. We measured primary productivity and the uptake of ammonium, nitrate, urea, and amino acids in two size fractions (> 3 μ m and approximately 0.7–3 μ m), as well as ammonium regeneration and nitrification using 15 N and 13 C tracer approaches in the near‐shore waters of the Chukchi Sea, during January, April, and August for two consecutive years. At discrete depths, nitrate comprised 46–78% of the total dissolved N pool during January and April but only 2–6% during August. Dissolved organic N (DON) concentrations increased between January and August though the carbon (C) : N (mol : mol) of the DON pool declined. Of the substrates tested, amino acids supported the bulk of both N and C nutrition in both size fractions during January and April (ice‐covered). Urea generally had the lowest uptake rate under ice‐covered conditions; uptake of urea‐C was only detectable in August. Though previous Arctic studies focused largely on nitrate, we found nitrate uptake was generally lower than other substrates tested. The sharp decline in nitrate concentration between April and August, however, indicates a drawdown of nitrate during that period. Rates of ammonium uptake were highest in August, when it was the dominant N substrate used. During all sample periods, rates of ammonium regeneration were sufficient to supply ammonium demand. Rates of nitrification varied between sample periods, however, with much higher rates seen in January and April.